Syndrome of Transient Headache and Neurologic Deficits With Cerebrospinal Fluid Lymphocytosis (HaNDL): A Pediatric Case Report. (December 2013) - Gonçalves, Daniel; Meireles, Joana; Rocha, Ruben; Sampaio, Mafalda; Leão, Miguel
The syndrome of transient headache and neurologic deficits associated with cerebrospinal fluid lymphocytosis (HaNDL) is characterized by 1 or more episodes of severe headache, transient neurologic deficits, and lymphocytic pleocytosis in the cerebrospinal fluid. It is a benign and self limited disorder seldom reported in pediatric age. We report the case of a 14-year-old girl who suffered from 2 episodes of headache with transient focal neurologic deficits and pleocytosis consistent with the syndrome of HaNDL. This entity should be taken into account as a differential diagnosis in otherwise healthy children presenting with recurrent headache and acute neurologic deficits. Repeated use of invasive and expensive laboratory and imaging investigations can be avoided when the diagnosis of the syndrome of HaNDL is correctly established.